2005
DOI: 10.1111/j.1600-051x.2005.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of interleukin‐17 in the immunopathology of periodontal disease

Abstract: These results indicate that IL-17 is produced in periodontal lesions, which may be involved in Th1 modulation and enhance inflammatory reactions via gingival fibroblast-derived mediators in periodontal disease. Thus, IL-17, together with other cytokines, has a potential role in the aetiopathogenesis of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
173
5
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(205 citation statements)
references
References 44 publications
(61 reference statements)
17
173
5
10
Order By: Relevance
“…De acuerdo con el estudio de Takahashi et al (14), la IL-17 se produce en la lesion periodontal y puede tener un papel activo en la etiopatogenia de la enfermedad periodontal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…De acuerdo con el estudio de Takahashi et al (14), la IL-17 se produce en la lesion periodontal y puede tener un papel activo en la etiopatogenia de la enfermedad periodontal.…”
Section: Discussionunclassified
“…Takahashi et al (14) demostraron que IL-17 es producida localmente por las célu-IL-17 Inmunoassay, Quantikine, R&D, Inc, Minneapolis, USA. The statistical data was analysed by Stata 7.0 using an unpaired Student t-test.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-γ induces macrophage activation and the production of inflammatory mediators and it is also able to suppress the activity of Th2 cells 22 . Therefore, high levels of this cytokine have been related to periodontal disease progression [22][23] . Controversially, Santos et al 24 and Ribeiro et al 20 also found a higher expression of cytokines in patients with wellcontrolled diabetes and periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 is a pro-inflammatory cytokine produced by Th17 cells, which stimulates the production of proinflammatory mediators 23 . Chronic periodontitis sites have shown increased levels of IL-17 in comparison with healthy periodontal tissues [18][19][20][21][22][23] and periodontal pathogens can stimulate the production of IL-17 from T-cells 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation